Royal Geographical Society (with IBG) Medals and Awards celebration 2022. Issue 3 (8th August 2022) - Clifford, Nigel; Hempleman‐Adams, David; Francis, Jane; Cloke, Paul; Sidaway, James; Hannah, David
Abstract: The Royal Geographical Society (with IBG) annual Medals and Awards recognise achievements in researching, communicating and teaching a wide range of geographical knowledge. The speeches and citations are a record of the 2022 celebrations, which occurred at the Society on 6 June 2022, with contributions from Sir David Hempleman‐Adams, Professor Dame Jane Francis, Professor Paul Cloke, Professor James Sidaway and Professor David Hannah.